2009
DOI: 10.1080/09540120802283469
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social impact and quality of life of people living with HIV/AIDS in South India

Abstract: This study examines psycho-social impact of HIV and quality of life of 646 HIV-infected persons from a major government sexually transmitted disease (STD) clinic in South India. In this cross-sectional study, data was collected using interview schedule and scales. Nearly 70% had problems in parenting their children after acquiring the infection. Most (88%) of the respondents reported of seeking help from their family members, relatives or close friends at the time of their illness. Among the four categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 23 publications
8
47
2
2
Order By: Relevance
“…Managing information of one's own HIV status or of a close family member is thus important as a strategy to escape from enacted stigma and its social costs (Pallikadavath et al, 2005;Steward et al, 2008). High disclosure-related concerns are supported by quantitative studies of stigma (Subramanian, Gupte, Dorairaj, Periannan & Mathai, 2009;Thomas, Rehman, Suryanarayanan, Josephine, Dilip, Dorairaj et al, 2005) with at least one study reporting significantly higher disclosure concerns among positive women (91%) than men (82%) (Subramanian et al, 2009). …”
Section: Article Originalmentioning
confidence: 63%
See 2 more Smart Citations
“…Managing information of one's own HIV status or of a close family member is thus important as a strategy to escape from enacted stigma and its social costs (Pallikadavath et al, 2005;Steward et al, 2008). High disclosure-related concerns are supported by quantitative studies of stigma (Subramanian, Gupte, Dorairaj, Periannan & Mathai, 2009;Thomas, Rehman, Suryanarayanan, Josephine, Dilip, Dorairaj et al, 2005) with at least one study reporting significantly higher disclosure concerns among positive women (91%) than men (82%) (Subramanian et al, 2009). …”
Section: Article Originalmentioning
confidence: 63%
“…By comparison, perceived or felt stigma is reported much higher. For example, more than 94% of men and women reported perceived stigma in two separate studies by Thomas et al (2005) and Subramanian et al (2009). Quality of life of those experiencing enacted stigma was found to be good in overall terms.…”
Section: Article Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…8,17 Some studies showed that married individuals had better quality of life as compared to the single individuals. [18][19][20] Majority of the single individuals were males in our study. In a society like that of India, responsibility of providing for the family falls heavily on the father or the husband.…”
Section: Discussionmentioning
confidence: 99%
“…Social support which defined as the fighting spirit against AIDS was significantly associated with healthrelated quality of life (Nunes et al 1995). It places great emphasis on the subjective feelings of infectors and can evaluate the therapeutic effect of AIDS more comprehensively than the traditional objective indicators such as mortality or CD4+ T lymphocytes (Subramanian et al 2009). It also can provide a comprehensive basis to screen for intervention measures and health resource allocation decisions (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%